The Role of Arabic Language in Early Childhood: A Phenomenological Study of Millennial Madurese Families In Kubu Raya - Muhammad Amin Khalil; Abu Bakar; Bariq Alaydrus; Lailatul Fitri (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This article aims to examine the role of Arabic in early childhood within the context of millennial Madurese families in Kubu Raya, West Kalimantan Province. This study uses a qualitative approach with a phenomenological method to gain an in-depth understanding of parents’ experiences and practices in introducing and habituating the use of Arabic to early childhood. The primary data was obtained from five millennial Madurese parents who have early childhood in Kubu Raya Regency. Data were collected through in-depth interviews, observation, and documentation techniques, supported by secondary data in the form of literature relevant to early childhood education, bilingualism, and Arabic language learning. The data collection process was carried out gradually and continuously throughout November 2025. Data analysis was conducted qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that millennial parents in Madura introduce Arabic to young children through various parenting strategies, such as integrating the language into daily activities, modelling behaviour, religious activities, and utilising digital media such as YouTube videos with parental guidance. Arabic is positioned not only as a tool for linguistic mastery but also as a medium for character formation and the internalisation of Islamic values. This study emphasises that the quality of interaction, consistency in parenting, and the family environment are key factors in the successful introduction of Arabic to early childhood.